The Health of Nations: Three Essays In Health Economics - Kayembe, Lidia (Université d'Ottawa / University of Ottawa, 2014)
Three essays form this thesis which addresses the effectiveness of interventions aimed at attaining two health Millennium Development Goals (MDG) set by the United Nations: a 2/3rds reduction by 2015 of 1990 child mortality rates (MDG4) and 3/4th reduction of 1990 maternal mortality rates by the same date (MDG5). The first chapter assesses the relative efficiency of 85 countries at using these interventions for the reduction of child and maternal mortality. It teases out the extent to which mortality reduction is a result of the interventions themselves as opposed to the context in which they are implemented. A three step procedure which includes Data Envelopment Analysis indicates that efficiency is mainly driven by context. Chapter 2 addresses the association between the 2000-2008 rates of change of interventions and the rate of change of mortality. It uses finite mixture modeling to take account of the possibility that there may be underlying heterogeneity in the mortality reduction functions of the 32 sub-Saharan African countries studied. Results support this hypothesis and show that an intervention may exhibit increasing returns to scale in some countries and decreasing returns to scale in others. Chapter 3 assesses the link between interventions and mortality rates and examines cost minimizing scenarios for attaining MDG4 and MDG5 in 27 sub-Saharan African countries. Lagged data on interventions predicts mortality rates (by OLS) to take into account the potential reverse causality between the two. Results indicate that achieving MDG mortality targets at the least possible cost invariably requires very substantive increases in medical human resources, yet training physicians has not been the main objective of public health organizations. Furthermore, improving the context in which interventions are implemented - increasing female literacy or effectiveness of political stability- allows countries to reach mortality targets with substantially lower levels of interventions (including, much lower levels of physician density).
Keywords: efficiency; effectiveness; millennium development goals (MDG); health MDG interventions